The Future Leader - Morgan, Jacob (Ascent Audio, 2020)
There has been a lot written about leadership for the present day, but the world is changing quickly. What worked in the past won't work in the future. We need to know how to prepare leaders who can successfully navigate and guide us through the next decade and beyond. How is leadership changing, and why? How ready are leaders today for these changes? What should leaders do now? To answer these questions, Jacob Morgan interviewed over 140 CEOs from companies like Unilever, Mastercard, Best Buy, Oracle, Verizon, Kaiser, KPMG, Intercontinental Hotels Group, Yum! Brands, Saint-Gobain, Dominos, Philip Morris International, and over a hundred others. Jacob also partnered with Linkedin to survey almost 14,000 of their members around the globe to see how CEO insights align with employee perspectives. The majority of the world's top business leaders that Jacob interviewed believe that while some core aspects of leadership will remain the same, such as creating a vision and executing on strategy, leaders of the future will need a new arsenal of skills and mindsets to succeed. What emerged from all of this research is the most accurate groundbreaking book on the future of leadership, which shares exclusive insights from the world's top CEOs and never before seen research.